Danny and the dinosaur - Hoff, Syd, 1912-2004. ([New York, NY] : Harper Trophy, 1993)
A little boy is surprised and pleased when one of the dinosaurs from the museum agrees to play with him.
"Newly illustrated edition"--T.p. verso.
Keywords: Dinosaurs -- Fiction